Effects of collaborative monitoring and adaptive management on restoration outcomes in dry conifer forests - Barrett, Kevin J., author; Cannon, Jeffery B., author; Schuetter, Alex M., author; Cheng, Antony S., author; Elsevier B.V., publisher (Colorado State University. Libraries, 2021)
In response to large, severe wildfires across the western US, federal initiatives have been enacted to increase the pace, scale, and quality of ecological restoration in fire dependent forests. To address uncertainty and controversy in agreement among specific restoration prescriptions on national forest land, several initiatives adopt a collaborative adaptive management (CAM) strategy wherein monitoring data can inform stakeholder input into future management actions. It is unclear, however, how such approaches may change restoration outcomes. Here we assess the extent to which CAM strategies impact restoration outcomes that were implemented as part of the Collaborative Forest Landscape Restoration Program (CFLRP) in ponderosa pine-dominated forests of the Colorado Front Range. We assessed stand-level desired conditions across 24 projects over a 7-year period to determine how restoration treatments contribute to desired conditions, and compared treatment outcomes over implementation time to assess whether the CAM processes contribute towards treatments better approximating restoration. We found that restoration treatments improve aspects of forest structure related to stand density. However, meeting objectives related to forest composition and horizontal structural complexity goals were not met. Additionally, CAM processes were effective at improving outcomes related to forest density over implementation time, but novel tools and approaches may be required so that outcomes related to forest composition and horizontal structural complexity are more congruent with restoration objectives. Evaluating the success and challenges of CAM provides insight to improve collaborative and large-scale restoration.
Keywords: Pinus ponderosa; collaborative adaptive management; forest structural heterogeneity; collaborative forest landscape restoration; ecological restoration; Pseudotsuga menziesii; Colorado Front Range